Toward Pediatric T Lymphoblastic Lymphoma Stratification Based on Minimal Disseminated Disease and NOTCH1/FBXW7 Status. Issue 10 (6th October 2021) - Trinquand, Amélie; Plesa, Adriana; Abdo, Chrystelle; Subtil, Fabien; Aladjidi, Nathalie; Rigaud, Charlotte; Touzart, Aurore; Lhermitte, Ludovic; Petit, Arnaud; Michaux, Katell; Jung, Charlotte; Chassagne-Clement, Catherine; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : While outcome for pediatric T lymphoblastic lymphoma (T-LL) has improved with acute leukemia-type therapy, survival after relapse remains rare. Few prognostic markers have been identified: NOTCH1 and/or FBXW7 ( N/F ) mutations identify good prognosis T-LL and high-level minimal disseminated disease (MDD) is reported to be of poor prognosis. We evaluated MDD and/or MRD status by 8-color flow cytometry and/or digital droplet PCR in 82 pediatric T-LL treated according to the EURO-LB02 prednisone reference arm. Both techniques gave identical results for values ≥0.1%, allowing compilation. Unlike historical studies, an MDD threshold of 1% had no prognostic significance. The 54% (42/78) of patients with MDD ≥0.1% had a relatively favorable outcome (5-y overall survival [OS] 97.6% versus 80.6%, P = 0.015, 5-y event-free-survival [EFS] 95.2% versus 80.6%, P = 0.049). MDD lower than 0.1% had no impact in N/F mutated T-LL, but identified the N/F germline patient with a high risk of relapse. Combining oncogenetic and MDD status identified 86% of patients (n = 49) with an excellent outcome and 14% of N/F germline/MDD <0.1% patients (n = 8) with poor prognosis (5y-OS 95.9% versus 37.5%, P < 0.001; 5y-EFS 93.9% versus 37.5%, P < 0.001). If confirmed by prospective studies, MDD and N/F mutational status would allow identification of a subset of patients who merit consideration for alternative front-line treatment.